Evidence based management of intracapsular neck of femur fractures - Hoskins, W; Webb, D; Bingham, R; Pirpiris, M; Griffin, X (SAGE Publications, 2017)
Neck of femur fractures are occurring at an increased incidence. Functionally independent patients without cognitive impairment can expect reasonable life expectancy. This indicates the need for a durable surgical option that optimises the chance to return to pre-injury functional status, with minimal risk of complications and reoperation. Most fractures are displaced. Surgical options include internal fixation, hemiarthroplasty or total hip arthroplasty (THA). Evidence is conclusive that arthroplasty options outperform internal fixation in terms of function, quality of life and reoperation rates. In anyone other than young patients where head preserving surgery is required, arthroplasty is the standard of care. Hemiarthroplasty is the heavily favoured arthroplasty option for surgeons. However, in patients other than the extreme elderly, medically infirm, neurologically impaired, or with little or no ambulatory capacity, the evidence to support hemiarthroplasty is lacking. In functionally independent patients without cognitive impairment, THA should be considered the gold standard, producing better functional and quality of life outcomes, lower reoperation rates and better cost effectiveness, with no difference in complications or mortality. An increased risk of dislocation does exist. This may be reduced with modern surgical technique and implant options. Low amounts of research have been afforded to undisplaced fractures. For this fracture type, surgery is the standard of care. Despite a higher risk of reoperation, internal fixation is the preferred option for all age groups. Further study is required to identify the difference between internal fixation and THA, in particular, for unstable fracture patterns in elderly patients.